Organizational Building Blocks for Blockchain Governance: A Survey of 241 Blockchain White Papers - Honkanen, Petri; Nylund, Mats; Westerlund, Magnus (Frontiers in Blockchain, 2021)
Governance for centralized organizational structures has long roots and well-developed frameworks, including for various specialty areas such as IT or data governance. The introduction of blockchain technology as a supportive tool for implementing decentralized organizations requires a renewed focus for research in the area. The paper utilizes empirical data from blockchain ecosystems in the form of white papers (public communique of intention) to analyze their governance intentions. The empirical findings are based on a review of 241 blockchain and DLT white papers, out of which 67 include explicit descriptions of how governance is to be organized. In our empirical analysis, we distinguish between three categories of governance: objectives, mechanisms, and stakeholders. For these categories, we further identify 28 features in total, which are then described in an open encoding format. Hence, the paper contributes to the emerging field of blockchain research, and particularly to the decentralized aspects of blockchain governance research. This research also reveals that governance does not receive the attention it should as a large number of ecosystems have not disclosed their governance intentions. The results can be utilized as a framework for future research. The results can also be useful for industry when designing and developing governance systems.